THE EFFECT OF DICTOGLOSS STRATEGY ON THE LISTENING COMPETENCY OF THE TENTH GRADE STUDENTS AT SMA NEGERI 1 SUKASADA IN ACADEMIC YEAR 2016/2017 - Suprianti, G.A.P.; Pratama, I Putu Mega (International Journal of Language and Literature, 2017)
This study aimed at investigating whether or not there was any significant effect on students’ listening competency who were taught by dictogloss strategy and those who were taught by conventional strategy. The population of this study was the tenth grade students in SMA N 1 Sukasada. Two classes were taken as samples in this study using cluster random sampling technique. They were assigned as experimental group and control group by lottery. To obtain the required data, the two groups were given different treatments. The experimental group was taught by using dictogloss strategy, meanwhile the control group was taught by using conventional strategy (cloze listening strategy). To collect the data the instruments used in this study were the teaching scenario and post-test in the form of listening test. The obtained data were then analyzed descriptively and inferentially. The result of inferential statistics showed that the t-observed exceeded the t-critical value. Thus, the null hypothesis was rejected, which means there was significant effect on students’ listening competency who were taught by dictogloss strategy and those who were taught by conventional strategy.